(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
This article demonstrates the possibilities the digital offers in convening material across time and place, and the new insights into historical collections that are thereby enabled. Drawing on the 19th century Bleek and Lloyd Archive’s visual works, notebooks, and dictionary cards of the northern San ǃxun language, I show that the convenor, Lucy Lloyd, devised a referencing system that allows the material to span across restrictive categories, and beyond the physical limitations of the page. Through two of my own digital curations of selected ǃxun material, and material beyond the collection, I demonstrate how digital affordances enable the material to be read together across time and place, and following Lloyd’s referencing system, to be mutually informative, arguing that Lloyd organised the material in a way that almost anticipates digital affordances nearly 150 years later.